Investigating recycled filter media in order to remove fluoride compounds from groundwater - Boussouga, Youssef-Amine; Valentukevičienė, Marina; Zurauskienė, Ramunė (International Conference “Environmental Engineering”, 2017)
In this article, an enhanced recycled filter media for the removal of fluoride compounds from groundwater via filtration process was investigated. Experiments were made to investigate the influence of recycled filter media on removal efficiency of fluoride compounds. The recycled backwash cake based filter media used at Lithuanian water works were investigated in a pilot test-bench constructed for this research in the Water Management Laboratory of Vilnius Gediminas Technical University.